Peran Instagram dalam Pembentukan Identitas Remaja di Era Digital - Fauzan, Jeje; Harahap, Halomoan (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
This study aims to examine the role of Instagram in shaping and expressing adolescent self-identity in the digital era, with a focus on Cilegon City. Adolescence is a pivotal stage of identity development, where social media functions as a space for self-presentation, social validation, and relationship-building. Employing a qualitative approach with a phenomenological method, this research involved five adolescents aged 16–20 who were purposively selected based on their active Instagram use and engagement in digital interactions. Data were collected through account observation, in-depth interviews, and documentation of Instagram activities. The findings indicate that Instagram is utilized to construct an ideal self-image, express values and emotions, and gain social acknowledgment. However, the pressure to maintain a perfect appearance also triggers psychological risks such as anxiety and a disconnect between online and offline identity. These results demonstrate that Instagram serves not only as a medium for expression but also as a complex social arena in adolescent identity formation. The study underscores the necessity of digital guidance and adaptive media literacy to support adolescent mental health.